Core Academic Language Skills: validating a construct in linguistically dissimilar settings. Issue 1 (2nd January 2022) - MacFarlane, Marco; Barr, Christopher; Uccelli, Paola
ABSTRACT: Recently a novel instrument – the Core Academic Language Instrument (CALS-I) – aimed at testing a constellation of school-relevant English language skills was developed and validated for use in the United States (Uccelli, Barr, Dobbs, Galloway, Meneses and Sánchez, 2015. Core Academic Language Skills: An expanded operational construct and a novel instrument to chart school-relevant language proficiency in preadolescent and adolescent learners. Applied Psycholinguistics 36: 1077–1109). The unitary construct tested by the CALS-I was dubbed Core Academic Language Skills (CALS) and it aimed to identify and describe a set of skills that comprise academic language proficiency of high utility across curricular content areas. This study piloted a version of the CALS-I that was slightly modified for use in South Africa targeting specifically middle-school learners. The results of this study reveal that the CALS construct functions almost identically to the United States sample when tested in South Africa, and this provides strong evidence for the fundamental and cross-cutting nature of these pedagogically relevant skills.